The effects of upstream processing on the chemical profile and immunomodulating activity of Echinacea purpurea tinctures - Carty, Michael; Sheridan, Helen; Healy, Anne (My University, 2025)
Echinacea purpurea (L.) Moench is a medicinal plant that is widely known for its immunomodulating properties. There is a lack of understanding regarding how E. purpurea tinctures should be prepared to ensure the most favourable biological activity. To address this gap, a total of 24 tinctures of E. purpurea were prepared with fresh or dried plant material, that was chopped (>2000 μm) or shredded (500–2000 μm), and that was 2 or 3-years-old at the time of harvest. Tinctures contained herba or radix or a combination of both. The chemical profile of the tinctures was determined using HPLC coupled with a principal component analysis of 1H NMR data. This analysis revealed that tinctures prepared with dried plant material (n = 8) had significantly higher concentrations of caffeic acid derivatives than tinctures prepared with fresh plant material, with the exception of 4 tinctures. The immunomodulating ability of tincture extracts, at a concentration of 100 μg/mg, was evaluated in vitro using non stimulated and lipopolysaccharide (LPS)-stimulated immortalised bone marrow derived macrophages (iBMDM) and THP-1 cell lines. Tincture extracts containing dried plant material reduced IL-6 production in LPS-stimulated iBMDM and THP-1 cells and increased production of TNF-α in THP-1 cells to a greater extent than tincture extracts prepared with fresh plant material. Despite the absence of caffeic acid derivatives, a number of tincture extracts prepared with fresh and shredded plant material had significant anti-inflammatory activity. The in- clusion of herba in the tincture was seen to significantly inhibited IL-6 in both iBMDM and THP-1 cells. This study highlights the importance of selecting appropriate upstream processing methods to ensure the production of quality E. purpurea tinctures.
PUBLISHED
Keywords: Echinacea purpurea; Caffeic acid derivatives; Upstream processing; Principal component analysis; THP-1 cells; Immobilised bone marrow derived macrophages; Innate immunology; Other; Education